The Errors in the Variables Problem in the Cross‐Section of Expected Stock Returns - KIM, DONGCHEOL (Journal of Finance, 1995)
ABSTRACT Recent research has documented the failure of market beta to capture the cross‐section of expected returns within the context of a two‐pass estimation methodology. However, the two‐pass methodology suffers from the errors‐in‐variables (EIV) problem that could attenuate the apparent significance of market beta. This article provides a new correction for the EIV problem that is robust to conditional heteroscedasticity. After the correction, I find more support for the role of market beta and less support for the role of firm size in explaining the cross‐section of expected returns. While the EIV correction leads to a diminished role of firm size, the size variable remains a significant force in explaining the cross‐section of expected returns.